From visual attention to behavioural intention: A relational framework of culturally creative desserts in museum communication - Zichen Ke; Xiang Meng; Jingzong Xu; Muhizam Mustafa (PLoS ONE, 2026)
This study examines how the visual presentation of culturally creative desserts (CCDs), modelled after Chinese museum artefacts, relates to potential visitors’ visit-related behavioural intention under first-exposure, image-mediated conditions. Drawing on the AIDA model, this study develops a four-stage framework (VCVB: perceived Visual Attention, Curiosity, Visit Motivation, Behavioural Intention) to examine whether visual attention is directly associated with visit motivation in visually mediated museum contexts. A survey using image-based stimuli was conducted with 205 respondents and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results reveal an indirect-only pattern: perceived visual attention is positively related to curiosity, curiosity to visit motivation, and visit motivation to behavioural intention, whereas the direct association between visual attention and visit motivation is not significant. These findings indicate that the commonly assumed direct association between visual attention and motivational orientation does not hold under first-exposure, image-mediated conditions. Instead, visual attention operates indirectly through epistemic curiosity and visit motivation, suggesting that visually driven attention alone is insufficient to generate visit-related intention.